GE_GERICHTE P/15858/2018 vom 30. Juni 2021 - GE Cour de justice (2021)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE L'HONNEUR;FAIT JUSTIFICATIF | CPP.310.al1.leta; CP.14; CP.173; CP.174; LaCP.15